Penerapan Metode Cooperative Learning Pada Aplikasi Pembelajaran Siswa Berbasis Website - Gifari, Aqil Naufal; Darusalam, Ucuk (STMIK Budi Darma, 2022)
The school is a place where the teaching and learning process takes place where the school applies virtual learning, so that students easily feel bored when learning. There are many types of learning, and the problems that arise in the learning process are also diverse. In this study, problems in the learning process were still limited, and the delivery of material provided by the teacher made it difficult for students to understand, thereby reducing student interest in learning. Responding to this situation, the temporary results of the author succeeded in creating a website and doing graphic testing on the website that was created, which only 56 users could access. If there are 100 users accessing the website, the server will be down and the website cannot be accessed by anyone.